Determining effective subject-specific strength levels for forward dives using computer simulations of recorded performances - King, M. A.; Kong, P. W.; Yeadon, M. R. (Journal of Biomechanics, 2009)
This study used optimisation procedures in conjunction with an 8-segment torque-driven computer simulation model of the takeoff phase in springboard diving to determine appropriate subject-specific strength parameters for use in the simulation of forward dives. Kinematic data were obtained using high-speed video recordings of performances of a forward dive pike (101B) and a forward somersault pike dive (105B) by an elite diver. Nine parameters for each torque generator were taken from dynamometer measurements on an elite gymnast. The isometric torque parameter for each torque generator was then varied together with torque activation timings until the root mean squared (RMS) percentage difference between simulation and performance in terms of joint angles, orientation, linear momentum, angular momentum, and duration of springboard contact was minimised for each of the two dives. The two sets of isometric torque parameters were combined into a single set by choosing the larger value from the two sets for each parameter. Simulations using the combined set of isometric torque parameters matched the two performances closely with RMS percentage differences of 2.6% for 101B and 3.7% for 105B. Maximising the height reached by the mass centre during the flight phase for 101B using the combined set of isometric parameters and by varying torque generator activation timings during takeoff resulted in a credible height increase of 38 mm compared to the matching simulation. It is concluded that the procedure is able to determine appropriate effective strength levels suitable for use in the optimisation of simulated forward rotating dive performances.